Scale-invariant magnetic textures in the strongly correlated oxide NdNiO3 - Jiarui Li (Nature Portfolio, 2019)
The many strongly interacting degrees of freedom in transition metal oxides make it difficult to capture and describe the nature of their metal-insulator transitions. Li et al. show that a resonant magnetic X-ray nanoprobe gives access to local critical behavior that is difficult to detect otherwise.